INTEGRATIVE MINISTERIAL TRAINING: A CASE STUDY IN THE BAPTIST TRADITION OF SOUTH AFRICA - M. Naidoo (Acta Theologica)
Relevant theological education for our context is key, and the sharing of best pedagogical practice can make theological education more sustainable in Africa. Many in theological education use the word “holistic” to describe integration in their curricula, yet with no clear consensus about what it exactly involves. This article reports on an action research on integrative curriculum development. It explores how the Baptist Theological College of Southern Africa intentionally brings together the major learning dimensions of academic excellence, vocational training, and spiritual formation in a holistic way. The article provides key findings and reflects on the institutional, denominational, and contextual challenges that shape curriculum design. This article positions integration as a key approach to curriculum design, as learning dimensions are intentionally linked for meaningful learning, rather than simply the mastery of fragmented information.